Origins of Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The causes of cerebral palsy were determined in a prospective study of 43,437 full term children from data collected in the Collaborative Perinatal Study of the National Institute of Neurological and Communicative Disorders and Stroke, Bethesda, MD, and published from the Department of Pathology and Center for Biostatistics and Epidemiology, M.S.